Edith Piaf : a cultural history - Looseley, David (Liverpool University Press, 2015)
The world-famous French singer Édith Piaf (1915-63) was never just a singer. This book suggests new ways of understanding her, her myth and her meanings over time at home and abroad, by proposing the notion of an 'imagined Piaf.